2008
DOI: 10.1007/s11999-008-0204-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Followup of Vascularized Fibular Grafting for Femoral Head Necrosis

Abstract: Vascularized fibular grafting has been used for treatment of osteonecrosis of the femoral head and although some reports demonstrate successful short- to mid-term outcomes, long-term results are still unknown. We retrospectively reviewed 135 patients (151 hips) who underwent vascularized fibular grafting for osteonecrosis of the femoral head. One-hundred and ten patients (124 hips) were followed for a minimum 10 years (mean, 13.9 years; range, 10-23.7 years). The mean Harris hip score improved from 72 to 88. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 33 publications
1
92
0
2
Order By: Relevance
“…There are multiple such treatment options directed toward preserving the femoral head and maintaining coxofemoral joint congruity to prevent or delay hip arthrosis [2,9]. Although technically complex, treatment by free vascularized fibular grafting (FVFG) is reportedly a biologic option for hip preservation that may last 20 years or longer [1,2,7,9,13,28]. It generally is accepted this intervention is more likely to result in hip preservation when performed before radiographic collapse of the femoral head [1,2,9,20,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple such treatment options directed toward preserving the femoral head and maintaining coxofemoral joint congruity to prevent or delay hip arthrosis [2,9]. Although technically complex, treatment by free vascularized fibular grafting (FVFG) is reportedly a biologic option for hip preservation that may last 20 years or longer [1,2,7,9,13,28]. It generally is accepted this intervention is more likely to result in hip preservation when performed before radiographic collapse of the femoral head [1,2,9,20,26].…”
Section: Introductionmentioning
confidence: 99%
“…First, in reported outcomes after FVFG, precollapse and postcollapse femoral heads have been grouped together when plotting graft survival and identifying risk factors for failure [19,[22][23][24][25][26]28]. Stage, size, and etiology have been identified as factors influencing the likelihood of hip preservation after FVFG [16,22,28], but it is not known whether these hold true in the specific subset of patients treated before bony collapse. Second, definitions of success and failure have been variable.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of FVFG lies in the combination of femoral head decompression, removal of necrotic lesion, introduction of osteoinductive cancellous bone, and vascularised cortical bone support of the subchondral surface [24]. There are multiple reports on the successful mid-and long-term outcomes of FVFG [7][8][9]. Zhang et al [8] used FVFG to treat 56 hips in 48 patients, with mean follow-up of 16 months.…”
Section: Discussionmentioning
confidence: 99%
“…The HHSs of all stages were improved, ranging from 11 to 13, and most femoral heads showed improvement (39 hips, 69.6%) or were at least unchanged (14 hips, 25.0%) on radiographs. Yoo et al [7] reported on 110 patients (124 hips) who underwent FVFG, with a minimum follow-up of ten years. Of these, 37 of 59 hips which were initially stage II hips and 39 of 65 stage III hips were found improved or unchanged radiographically at the latest follow-up, with mean HHS improved from 72 to 88.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation